Essential Oil from Flowers and Leaves of Elaeagnus Angustifolia (Elaeagnaceae): Composition, Radical Scavenging and General Toxicity Activities - Mohammadali Torbati; Solmaz Asnaashari; Fariba Heshmati Afshar (Tabriz University of Medical Sciences, 2016)
Purpose: The aim of this work was to identify the chemical composition of the essential oils obtained from the flowers and leaves of Elaeagnus angostifolia (Elaeagnaceae) along with evaluate the radical scavenging and general toxicity activities. Methods: A combination of GC-MS and GC-FID were utilized for analyzing the chemical profile of the essential oils extracted by hydro-distillation from the leaves and flowers of E. angustifolia. The essential oils were subjected to general toxicity and radical scavenging assays using brine shrimp lethality test and DPPH method, respectively. Results: In total, 53 and 25 components were identified and quantified in the essential oils of flowers and leaves, accounting for 96.59% and 98.97% of the oil, respectively. The both oils were observed to be rich in ester compounds. The most abundant components of the oil from flowers were E-ethyl cinnamate (60.00%), hexahydrofarnesyl acetone (9.99%), palmitic acid (5.20%) and phytol (3.29%). The major constituents of the oil from leaves were E-ethyl cinnamate (37.27%), phytol (12.08%), nonanal (10.74%) and Z-3-hexenyl benzoate (7.65%). Both oils showed moderate activity in DPPH assay; however, they exhibited potent tocixity in brine shrimp lethality test. Conclusion: The remarkable toxicity effects of the oils are worthy to further investigation to find the probable mechanisms of action accountable for the noticeable toxic effect of these essential oils.